Currency Wars Yesterday and Today - Brahmbhatt, Milan; Canuto, Otaviano; Ghosh, Swati (World Bank, Washington, DC, 2012)
An energetic debate on the danger of a global currency war has flared up in recent months, stoked by a renewed move to 'quantitative easing' in the United States, resurgent capital flows to developing countries and strong upward pressure on emerging market currencies. This economic premise views some of the arguments and concludes that the current United States monetary easing is a useful insurance policy against the risk of global deflation. But it is increasing pressure on developing countries to move toward greater monetary policy autonomy and exchange rate flexibility, as well as to undertake the institutional and structural policies needed to underpin such flexibility. Such reforms will take time.